FORMULATION AND EVALUATION OF TRAMADOL HYDROCHLORIDE-LOADED NIOSOMAL GEL BY ETHER INJECTION METHOD - Amreen, Amena; KV, RATNAMALA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The primary goal of this study was to develop a topical gel containing tramadol hydrochloride-loaded Niosomes injection technique as the vesicular carrier for site-specific delivery. Methods: The tramadol hydrochloride-loaded niosomes were created by varying the ratios of nonionic surfactants (Tween 80, Tween 60, Tween 20, Span 20, Span 60, and Span 80) and cholesterol while keeping the drug concentration constant. Results and Discussion: Each formulation was examined for drug content, entrapment efficiency, mean vesicular diameter, zeta potential, and in-vitro drug release tests. Among the six formulations, the N2 formulation containing the drug and Tween 20 demonstrated maximal drug content of 96.7%, entrapment efficiency of 99%, mean vesicular diameter of 319 nm, zeta potential of −28 mV, in-vitro drug release of 90.14% in 12 h, and the drug release followed the zero-order with non-fickian diffusion mechanism by ether injection method. As a result, the ether injection approach is an optimal procedure for the synthesis of tramadol hydrochloride niosomes. Conclusion: By comparing Niosomal gel with plain gel Niosomal gel indicated better results than plain gel.